Now you're in the sunken place - Peele, Jordan 1979- ([Variety Media], 2017)
A compilation of art inspired by the film "Get out". The majority of pieces collected in the glossy book were discovered on Instagram, where writer-director Jordan Peele found himself tagged in a stunning array of fan art as the film struck a chord with audiences following its February 2017 debut
Titel vom Buchrücken
Jordan Peele hat die Publikation zusammengestellt und das Vorwort verfasst
Free advertising supplement to the February 13, 2018 issue of "Variety"
Keywords: Schwarze -- Motiv; Kunst; Get out (Motion picture) / In art; Race in art; African Americans in art; Bildband